The Point of View in the Saudi Novel Between the Narrator and the Author: Selected Models - Al-Mozainy, Aliah Radatallah (Journal of Arabic Language Sciences and Literature, 2025)
This thesis examines “The Point of View in the Novel Between the Narrator and the Author”. It aims to study the relationship between the real author (novelist) and the fictional narrator in terms of the narrative work by considering three novels authored by Saudi novelists who have enriched the Saudi novel arena, yet their novelistic output has not been studied or brought into focus.The thesis is structured into a preface and two treatises: The preface introduces the concept of narrative point of view. The first treatise examines the concept of the narrator and the author (novelist), highlighting the differences between them, and explores the point-of-view angle in the three novels under consideration. The second treatise examines the potential presence of the real author in the narrative work and the forms of such presence.The thesis concludes a number of findings which I sum up in conclusion, the most important of which are: The narrator’s presence predominates over that of the author but does not negate it. The real author (novelist) may be found on the cover page, which Gérard Genette included in the editorial paratext (a division that all studies have followed, excluding the author). However, attributing this part solely to the publisher requires verification and reconsideration.
Keywords: Point of View; Author; Narrator; Paratext